Modified FMEA hazard identification for cross-country petroleum pipeline using Fuzzy Rule Base and approximate reasoning. (January 2022) - Hassan, Shamsu; Wang, Jin; Kontovas, Christos; Bashir, Musa
Abstract: The pipeline industry's existing and new safety challenges require flexible and powerful techniques for performing a risk-based analysis of cross-country petroleum product pipeline systems. One of the traditional tools for the prediction of pipeline failure is the Failure Mode and Effects Analysis (FMEA) technique due to its ease of application. However, many limitations have been identified in its application especially for cross-country pipelines in developing countries. Firstly, failure data is often either unavailable or unreliable, therefore identification of the risk priority numbers for the three failure factors ( i.e. probability of failure, severity and detection) relies on experts' elicitation. Secondly, domain experts often provide diverse opinions and knowledge, which could produce different assessment rankings and it is often difficult to harmonise due to the multidisciplinary nature of the FMEA team. Thirdly, there is a lack of a systematic way of accounting for the relative importance of individual failure factors, which carries the risk of the assessment results not representing the true risk picture of the assessed system. Consequently, this paper proposes a new approach, called the modified FMEA, by integrating the noted benefits of hybrid FMEA with Fuzzy Rule Base (FRB) and FMEA with Grey Relations Theory (GRT) in order to overcome the identified drawbacks. The study utilises both the fuzzy and the grey theory to include experts' diverse opinions and to assign a relative weighting to each assessment factor in the risk assessment. The results of the risk assessment are then used to determine the risk priority and rank the failure modes under different types of conditions. A case study of Nigeria's petroleum product pipeline system 2 B is conducted to examine the applicability and validity of the new approach. The results show the practical application of the methodology in this new domain. The new approach offers a more effective method for identifying product pipeline system hazards and risk analysis in geographies with limited or unreliable data. The application of this new methodology in the oil and gas cross-country pipeline domain will aid decision making under uncertainty for pipeline inspection and maintenance. Highlights: A hybrid technique is proposed to conduct pipeline risk analysis under high uncertain external conditions. A case study analysis of Nigeria's petroleum product pipeline system 2 B shows the application of the methodology. It provides an opportunity to incorporate experts' experience and knowledge when data is limited or uncertain. The failure factors with the most impact on the results are appropriately captured.